Brighter beginnings for teachers - Pullen, Patty, 1938- (ScarecrowEducation, 2004)
"Written in question-and-answer format, this book is of interest to special and regular education teachers, kindergarten through high school. It can also be used as a supplementary text in teacher education programs and for induction programs in school systems."--Jacket